Chronic Kidney Disease: Potassium and Your Diet - Ashley R. Kendall; Nancy J. Gal; Wendy J. Dahl (EDIS, 2016)
Potassium is an essential mineral required for normal body function. It helps maintain normal blood pressure, fluid and electrolyte balance, muscle and nerve function, as well as bone density. This 3-page fact sheet describes potassium and its normal dietary importance, as well as the impact potassium levels have on those with Chronic Kidney Disease. Written by Ashley R. Kendall, Nancy J. Gal, and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, December 2016.